(untitled) (Indian Journal of Veterinary Pathology, 2025)
A 12-year-old female spitz dog was brought for necropsy to the Department of Veterinary Pathology, Ranchi College of Veterinary Science and Animal Husbandry. On gross examination, liver showed multifocal white hard nodular growths ranging from 2 mm to 1.5 cm in diameter. Both lungs showed few nodular lesions in diaphragmatic lobe. On histopathological examination, liver parenchyma showed presence of anaplastic cells distributed in lobular and multifocal ductal structures suggestive of cholangiocellular carcinoma. There was marked proliferation of fibrous connective tissue in portal area, suggesting initiation of cirrhotic changes. Microscopically, metastatic lesion of cholangiocarcinoma was observed in heart. Significant metastatic changes and venous tumor thromboemboli were also observed in lungs. Simultaneous occurrence of cholangiocellular carcinoma along with metastasis in heart is a rare condition.